Rancang Bangun Sistem Pencampur Bahan Minuman Bersoda Berdasarkan Kadar Keasaman Berbasis PLC OMRON CP1H-XA40DR-A - Rindi Kusumawardani; Raden Sumiharto (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2015)
Have been made a prototype of soft drinks mixing ingredients system based on acidity controled by PLC OMRON CP1H-XA40DR-A. This system have been made based on the importance of pH levels on soft drinks. This mixing ingredients system has Human Machine Interface (HMI) for control and input on the system. High accuracy is needed in the process of mixing the ingredients of soft drinks to mantain the quality of the product. One of the factor that is considered to mantain it quality is to ensure pH levels of the mixing to standard production. The automation of soft drinks mixing ingredients systems is based on PLC by OMRON with serial number CP1H-XA40DR-A. This system equipped with eTape height sensor to detect height of the fluid, motor washer to pump the fluid, pH electrode PE-03 sensor to read the acidity.  The results of this study is a soft drinks mixing ingredients systems that automatically mixes the fluid according to the pH input by user. There are a range of acidity options available in this system, pH 4 to pH 6. The accuracy of the fluid mixing process is equal to 98,45%.